Ochotona hyperborea - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
10. Northern Pika Ochotona hyperborea French: Pika de Sibérie / German: Nordlicher Pfeifhase / Spanish: Pica de Siberia Other common names: Anadyr Northern Pika (minima), Chukchi Northern Pika (hyperborea), Lower Indigirka Northern Pika (shaman), Northern Baikal Northern Pika (davanica), Rusty Northern Pika (ferruginea), Tuva Northern Pika (stenorostrae), Ural Northern Pika (uralensis) Taxonomy. Lepus hyperboreus Pallas, 1811, “terris Tschuktschicis [= lands of Chukchee],” Chukotka Autonomous Okrug, Russia. According mtDNA and nDNA, O. hyperborea belongs to subgenus Pika. Taxonomic status of O. hyperborea as a species and of some taxa included herein was discussed for a long time. Ochotona hyperborea was included in O. alpina by several authors. Taking into account sympatry between these species and difference in chromosomes, two species were separated; however, svatoshi was listed as a subspecies of O. alpina in several checklists. Ochotona turuchanensis also was separated from O. hyperborea. The nominate subspecies of O. mantchurica again was considered a subspecies of O. hyperborea. Modern studies of morphology, genetics, and bioacoustics support composition of the species considered here. All of this taxonomic confusion required careful attention to published data on ecology. Ochotona hyperborea is closely related species to O. mantchurica and O. hoffmanni; these three species correspond to allospecies. One of the best taxonomical markers, correlated with genetic variation is bioacoustics. Several types of calls have distinct geographical variation. According to morphological study it includes cinereoflava, cinereofusca, davanica, ferruginea, kolymensis, litoralis, minima, naumouvi, normalis, shamani, stenorostrae, svatoshi, uralensis, yesoensis, and yoshikurai. Ochotona hyperborea is sympatric with O. alpina within Western and Eastern Sayan Mountains, Khangai Upland, and Tannu Ola Range (Tuva, Russia); sympatric with O. turuchanensis in the Putorana Plateau and adjacent regions of the central Siberian ...